Refleksje o sobie samym w korespondencji starego Grzegorza z Nazjanzu - Widok, Norbert (Vox Patrum, 2011)
Beside his speeches and poems, Gregory of Nasiansus left 245 letters. Over 160 of them were written in the last decade of his life, when after two years of his work as a bishop in Constantinople he returned to the country where he grew up. An object of analysis in this article are his texts related to ageing, which was often described by him in his letters. Gregory was aware of his old age and ensuing consequences such as sickness, the need for silence, the awareness of approaching death and requests for prayer sent to addressees. A number of passages taken from these letters reveal one of the many aspects of Gregory’s silhouette. In majority of essays describing his person and output he is shown as an eminent theologian, a rhetorician, a bishop, and even a mystic, who contributed greatly to the development of the theology of that epoch. My article presents Gregory as a man of „flesh and blood”, in his suffering and sickness very close to all subject to vicissitudes of life. Writing about himself as an elderly man, he became a brother of all ageing. The readers of his correspondence, both his addressees living in the fourth century and contemporary readers, may find a particular consolation in the experiences of the one recognized as a saint.